Violence against women: a literature review (Research, Society and Development, 2021)
Violence is any act of aggression or negligence against a person, group or community, which produces or may produce psychological harm, physical or sexual suffering, including threats, coercion or arbitrary deprivation of liberty, both in the public and private spheres. In an attempt to understand the factors that lead to violence against women, a literature search was carried out, through the digital platforms BVS and Lilacs, using the descriptors: violence against women, marital violence, intimate partner violence, domestic violence, 20 articles were selected, where variables were studied and correlated: profile of the victim and aggressor, type of violence committed, place of violence, involvement with alcohol. Due to its multifaceted character, violence against women is a social, political, economic and health problem, requiring, therefore, the integration of knowledge and service. The prevalence was observed in younger, black women, with low education, with the partner as the main aggressor, the most frequent place was the victim's home and the main reason for the aggression was the association with alcohol in relation to the type of aggression, the association of physical, sexual and psychological forms were the most prevalent.